Clinicopathological features and menin expression of pancreatic neuroendocrine neoplasm associated with multiple endocrine neoplasia type 1. (14th May 2020) - Sonoda, Akari; Yamashita, Yo‐ichi; Kondo, Tatsuya; Hayashi, Hiromitsu; Imai, Katsunori; Higashi, Takaaki; Yamamura, Kensuke; Yamao, Takanobu; Hashimoto, Daisuke; Baba, Hideo
Abstract: Background/Purpose: We examined therapeutic strategies for pancreatic neuroendocrine neoplasm (pNEN) associated with MEN1 (M‐pNEN) by investigating clinicopathological features and menin expression. Methods: Seventy‐seven patients who underwent resection of pNEN at our department from January 2001 to December 2017 were retrospectively analyzed. Immunohistochemical analysis of menin was performed using resected specimens. Results: Seven patients (9%) met the diagnostic criteria for MEN1. M‐pNEN had more tumors ( P < .01), a higher recurrence rate ( P = .028), and higher residual pancreatic recurrence ( P < .01) than sporadic pNEN (S‐pNEN). There were no significant differences in tumor size, lymph node metastasis, or World Health Organization grade between the two groups. Reduced menin staining in the tumor nuclei was found in 86% of M‐pNEN; whereas only 34% of S‐pNEN showed decreased nuclear staining. The remainder (66%) showed strong nuclear staining similar to normal islet cells ( P = .0071). Furthermore, four patients (57%) with MEN1 had many microadenomas with reduced nuclear menin staining. Overall survival of M‐pNEN patients was significantly better than S‐pNEN patients ( P = .049). Conclusion: M‐pNEN patients tend to develop spatially and temporally multifocal pNENs. However, M‐pNEN patient prognosis is good with repeated surgeries at recurrence. Therefore, minimal resection with strict follow‐up is recommended rather than extensive pancreatic resections for consideration of recurrence in M‐pNEN. Abstract : This study aimed to describe therapeutic strategies for pancreatic neuroendocrine neoplasm associated with multiple endocrine neoplasia type 1 (M‐pNEN) by investigating the clinicopathological features and menin expression. Sonoda and colleagues concluded that minimal resection with strict follow‐up is recommended rather than extensive pancreatic resections for consideration of recurrence in M‐pNEN.